PROGRAM TAHFIDZ 30 JUZ DALAM MEMBENTUK KARAKTER RELIGIUS DI SD SYAFANA ISLAMIC SCHOOL TANGERANG SELATAN - Suryani, Irma; Muh Ubaidillah Al Ghifary S; Pahrurroji (STAI Pelabuhan Ratu, 2024)
This study aims to analyze the method of forming religious character, the religious character that emerges, and the supporting and inhibiting factors in the formation of religious character through the 30 juz tahfidz program at SD Syafana Islamic School, South Tangerang. This study uses a descriptive qualitative method. The primary data sources were obtained through observation and interviews with the principal, teachers and students regarding the method of forming religious character, the religious character that emerges, and the supporting and inhibiting factors in the formation of religious character through the 30 juz tahfidz program at SD Syafana Islamic School, while the researcher obtained secondary data from books, journals, and other data sourced from the internet. The results of the study show that, 1. The methods used by the 30 juz tahfidz program at SD Syafana Islamic School in forming religious character are the lecture method, circle method, exemplary method, habituation method, advice method, story method, reward and punishment method, monitoring and evaluation. 2. The values of religious character formed through the 30 juz tahfidz program include five, namely the value of worship, the value of jihad, the value of trust and sincerity, the value of morals and discipline, and the value of exemplary behavior. 3. Supporting and inhibiting factors in the formation of religious character through the 30 Juz tahfidz program include the personality of the students themselves, family, school environment, community environment, and mass media.